Comparative Study of Minangkabau Women’s Inheritance Rights in Diaspora and the Homeland - Luthfia Ahluljannati Hamdi; Nisa Fitriani (Hikmah, 2026)
This study examines the differences in the inheritance rights of Minangkabau women living abroad versus those living in their hometowns, within the context of the interplay between matrilineal customary law and Islamic legal principles. The study aims to conduct a comparative analysis of Minangkabau women’s inheritance rights, focusing on two main aspects: high-ranking ancestral property and low-ranking ancestral property. The methodology employed is a descriptive qualitative approach with systematic analysis of inheritance practices across various social contexts. The results indicate that regarding high-value ancestral property, there is no difference between Minangkabau women living abroad and those in their hometowns, as they remain bound by the matrilineal system and the maternal lineage. However, regarding low-value ancestral property, differences emerge, with women living abroad tending to follow local customs. Meanwhile, in their hometowns, the distribution of low-value ancestral property generally adheres to Islamic faraid law, although individual needs are still considered through family deliberation. These findings demonstrate the flexibility of Minangkabau inheritance practices as a form of adaptation to social change without abandoning traditional and Islamic values. The implications of this research underscore the importance of harmonizing tradition and Islamic law in maintaining justice and the sustainability of the inheritance system.